The Effect of Holding Time on Stress Relief Annealing Process to Hardness of Carbon Steel SA.106 Grade B After Welding - Syukran Syukran; Azwinur Azwinur; Ferdiyansyah Ferdiyansyah (University of Muhammadiyah Jakarta, 2020)
Stress relief annealing (SRA) is a process of releasing residual stresses contained in the material due to the welding process. The need for SRA is due to heterogeneous changes in the microstructure when the material is exposed to the heat of welding so that it will cause the mechanical properties of the material to change. One of the mechanical properties that experience significant changes is hardness (hardness value) because it can experience an increase. Therefore it is necessary to decrease the hardness value through a heat treatment SRA that takes into account the appropriate holding time. The purpose of this study was to determine the effect of holding time variations on the value of the welding material hardness for the carbon steel case SA.106 Gr.B. During this time after welding SA106 material specifically under 19 mm thickness is not heat treatment after welding even though the welding effect will change the properties of this material, so it is necessary to heat treatment with certain holding time variations to determine its effect on the mechanical properties of the material. The welding process uses SMAW with E7018 electrodes. Specimen heating is carried out in a heating oven to a constant temperature of 650oC with variations in the heating time of 15 minutes, 30 minutes, and 45 minutes. Furthermore, hardness testing is done by testing the base metal area, heat affect zone, and weldment. The results that SRA greatly influenced the hardness value of a welded material, based on testing the highest hardness value in the SRA heat treatment was obtained at a holding time of 45 minutes with a hardness value on the base metal of 67 HRC (BM), HAZ area of 65.25 HRC, and weldment area of 64.42 HRC. But at the holding time for 45 minutes, the value of material hardness tends to be more uniform compared to other variables.